TORC2/3-mediated DUSP1 upregulation is essential for human decidualization. Issue 5 (May 2021) - Xu, Chunfang; Zhao, Weijie; Huang, Xixi; Jiang, Zhuxuan; Liu, Lu; Cui, Liyuan; Li, Xinyi; Li, Dajin; Du, Meirong
Abstract : Decidualization is the functional transformation process of endometrium in response to ovarian steroids dedicated to support embryo development. Defective decidualization is closely associated with various pregnancy complications such as recurrent miscarriage (RM). Dual specificity MAPK phosphatases (MKPs) are a family of phosphatases specifically regulating mitogen-activated protein kinase (MAPK) signaling with dual specificity for threonine and tyrosine. Here, using RNA-seq, we found that dual specificity phosphatase 1 (DUSP1) expression was prominently elevated among the MKP family members in db-cAMP treated primary human endometrial stromal cells (ESCs). We verified that its induction by db-cAMP in ESCs was in a dose- and time-dependent manner and that primary human decidual stromal cells (DSCs) present higher expression of DUSP1 than ESCs. A protein kinase A (PKA) inhibitor H-89 abolished its induction in ESCs, but not ESI-09, an EPAC1/2 inhibitor. Knock-down of TORC2/3 but not CREB by siRNA in ESCs diminished its induction by db-cAMP. Furthermore, knock-down of DUSP1, as well as TORC2/3 by siRNA caused abnormal activation of JNK during db-cAMP induction in ESCs, accompanied by decreased IGFBP1 expression, an ESC decidualization indicator, which could be fully rescued by a JNK inhibitor SP600125. In addition, Western blot showed that DUSP1 expression was reduced in the DSCs of patients with RM, along with JNK overactivation and decreased IGFBP1 expression. In conclusion, our results demonstrated that TORC2/3-mediated DUSP1 upregulation in response to the cAMP/PKA signaling safeguards IGFBP1 expression via restraining JNK activity, indicating its involvement in ESC decidualization, and that aberrant expression of DUSP1 in DSCs might engage in the pathogenesis of RM.